Optimization of biogas production from banana peels: Effect of particle size on methane yield - Tumutegyereize, P.; Muranga, F. I.; Kawongolo, J.; Nabugoomu, F. (African Journal of Biotechnology, 2011)
The matooke processing industry being set up by the Presidential Initiative on Banana Industrial Development (PIBID), once fully operational will generate much matooke associated waste that requires a sustainable waste handling mechanism. Anaerobic digestion of the peel waste for biogas production would provide a solution to that waste, but information on the pre-treatment of the matooke peel waste is inadequate. Hence, a study of the changes in the physicochemical characteristics of matooke peels under storage and optimization of particle size for biogas production was sought. Peels from five banana cultivars were analysed after one day, four and seven days of storage at ambient conditions. Peels of one cultivar were reduced to 1, 5 and 10 mm particle sizes and the other four cultivar peels were reduced to 1 mm of particle size. Peel storage pre-treatment of utmost four days was found to bring the carbon to nitrogen (C/N) ratio to the optimal range for anaerobic digestion of 10 to 32. C/N ratio was also found to be cultivar-dependent as it was significant at α = 0.05 between the different banana cultivars. A model of methane content depending on particle size was developed. A particle size of 6.73 mm was projected for optimum biogas production, although further validation of this model and optimal particle size is required with a bigger sample.
Keywords: Anaerobic digestion; Cooking banana cultivars; Optimal particle size; Peel storage; Specific methane yield